DIGITAL ENTREPRENEURSHIP MEWUJUDKAN GEN-Z BERKARAKTER - Ade Oki Pebiansyah; Rizaldi Putra; Lambok Rommy Sulaeman; Memet Sanjaya; Deni Utama; Salsabilla Khoirun Nissa; Reza Nugrahanto (Bajang Institute, 2024)
This community service (PKM) focuses on Digital Entrepreneurship as a means to realize generation Z with strong and innovative character. In a dynamic digital era, generation Z has great potential to become adaptive and creative entrepreneurs. This PKM activity aims to provide training and mentoring to high school and vocational students in utilizing digital technology to develop ethical and social impact business ideas. Through a practical approach, participants are taught digital entrepreneurship skills, such as digital marketing, BMC (Business Model Canvas) simulation. In addition, the program also emphasizes the importance of character values such as responsibility, integrity, and concern for the environment. The results of this PKM activity show a significant increase in the understanding and skills of digital entrepreneurship as well as the formation of strong character among generation Z, who are ready to face future economic challenges with a sustainable and ethical vision